2011
DOI: 10.3109/01480545.2011.557382
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating effect of lycopene and ellagic acid on 2,3,7,8-tetrachlorodibenzo-p-dioxin–induced spermiotoxicity and testicular apoptosis

Abstract: This study was conducted to investigate the prophylactic effects of lycopene (LC) and ellagic acid (EA) on 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-induced testicular and spermatozoal toxicity. These toxicological changes are associated with the oxidative stress and apoptosis in male rats. Forty-eight male rats were allocated to one of six groups of 8 rats each: control, LC, EA, TCDD, TCDD+LC, and TCDD+EA. The control group was treated with 0.5 mL/rat slightly alkaline solution+0.5 mL/rat corn oil every othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
(66 reference statements)
2
10
0
1
Order By: Relevance
“…There were increases in the number of TUNEL-positive cells, but not significantly, in the germinal epithelium of the testis of rats exposed to CTD for 90 consecutive days in a dose-dependent manner. It has been reported (Ates°s°ahin et al, 2010;Sönmez et al, 2011) that an increase in apoptotic germ cells is shown after exposure of different environmental pollutants associated with increased LPO. Bal et al (2012a) have reported that only 32 mg/kg of NOAEL dose of CTD, but not lower than the NOAEL dose (2 and 8 mg/kg), caused a significant increase in AI in the testis of developing rats.…”
Section: Discussionmentioning
confidence: 98%
“…There were increases in the number of TUNEL-positive cells, but not significantly, in the germinal epithelium of the testis of rats exposed to CTD for 90 consecutive days in a dose-dependent manner. It has been reported (Ates°s°ahin et al, 2010;Sönmez et al, 2011) that an increase in apoptotic germ cells is shown after exposure of different environmental pollutants associated with increased LPO. Bal et al (2012a) have reported that only 32 mg/kg of NOAEL dose of CTD, but not lower than the NOAEL dose (2 and 8 mg/kg), caused a significant increase in AI in the testis of developing rats.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that lycopene reduces lipid peroxidation levels, regulates antioxidant enzyme activities and sperm parameters by the studies examining the effects of lycopene against testicular toxicity caused by cisplatin (Ateşşahin, Karahan, Türk et al, ), adriamycin (Ateşşahin, Karahan, Yılmaz, Çeribaşı, & Bulmuş, ), ischaemia/reperfusion (Hekimoglu et al, ), cyclophosphamide (Çeribaşi, Türk, Sönmez, Sakin, & Ateşşahin, ; Türk, Çeribaşi, Sakin, Sönmez, & Ateşşahin, ) and 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin (TCDD; Sönmez, Türk, Çeribaşı, Sakin, & Ateşşahin, ). These studies showed significant reductions in sperm concentration, sperm motility and an increase in abnormal sperm rates in DEN‐treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…TCDD exposure can also lead to biochemical and pathological changes within the reproductive systems of male rats (Sonmez et al 2011;Beytur et al 2012). TCDD exposure is known to lead to infertility in humans and animals by increasing tissue damage and oxidative stress in the testis tissue and by adversely affecting sperm characteristics.…”
Section: Discussionmentioning
confidence: 99%